Indigenous agency in global systems - Eikeland, Sveinung (Journal of Rural Studies, 2021)
The article addresses expanding of global economic systems by studying Sámi strategies addressing Norwegian High Northern Policies (NHNP) launched by the Norwegian Ministry of Foreign Affairs from 2005. NHNP attracted global economy, labour and knowledge to the Arctic region. The Sámi responding are analysed by using agency theories in economic geography, and contributes to expand the content of agencies e.g. by understanding its embedding in specific historical shaped structures as well as in debates on new opportunity spaces in the wake of globalism. The study demonstrates three strategies debated and launched by the Sámi Parliament: (i) In grounding its resistance the Sámi Parliament argued that the entry of international industries into areas with Sámi population threaten the fundamental conditions for Sámi livelihood. (ii) By entering global governance the parliament emphasized the importance of Sámi negotiation with multinational companies in global governance frameworks. (iii) And by changing the historical understanding of Sámi territories in order to include research and higher education milieus outside remote rural districts.